2013
DOI: 10.1093/humrep/det239
|View full text |Cite
|
Sign up to set email alerts
|

Differences in quality of life and emotional status between infertile women and their partners

Abstract: This work was supported by Merck Sharp & Dohme (MSD), The Netherlands. There are no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
75
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 41 publications
12
75
4
2
Order By: Relevance
“…Therefore, being a female can predispose to suffer emotional maladjustment, which is in agreement with studies such as Huppelschoten et al (2013) that found that 63.8% of infertile females and 45.6% of infertile males had, at least, one risk factor for developing emotional maladjustment. It is no coincidence that most infertility literature is focused on women, since they are who receive medical treatment and are most likely to develop emotional disorders during assisted reproduction treatment (Chiaffarino et al, 2011;Culley, Hudson, & Lohan, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, being a female can predispose to suffer emotional maladjustment, which is in agreement with studies such as Huppelschoten et al (2013) that found that 63.8% of infertile females and 45.6% of infertile males had, at least, one risk factor for developing emotional maladjustment. It is no coincidence that most infertility literature is focused on women, since they are who receive medical treatment and are most likely to develop emotional disorders during assisted reproduction treatment (Chiaffarino et al, 2011;Culley, Hudson, & Lohan, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…4; show that infertile and fertile women have significantly different mental and emotional conditions: infertile women experience significantly harsher emotional conditions (Nilforooshan et al, 2008). Based on the results of some studies, in infertile couples, women experience more stress in comparison with their husbands (Chachamovich, Chachamovich, Ezer, Fleck, Knauth, & Passos, 2010;Huppelschoten, van Dongen, Verhaak, Smeenk, Kremer, & Nelen, 2013). Other similar studies report no significant differences in the mean score of quality of life in infertile women.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Infertility can lead to a lot of problems for women, most notably reduce their quality of life (Huppelschoten et al, 2013). Women make up more than half of the population and are the foundation of the health of the family and community.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There are gender differences in response to infertility. In a study of Dutch couples experiencing infertility, women had lower levels of quality of life than their partners [27].…”
Section: Significance and Backgroundmentioning
confidence: 99%
“…Thus, designing and conducting supportive programs play an important role in providing quality care for them [29]. Culturally sensitive assessment of the woman's partner, extended family, and social support network is important as a means to ascertain levels of social support that may mediate the experience's effects and enhance their sense of wellbeing [26][27][28].…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%